Human dendritic cell targeting peptide can be targeted to porcine dendritic cells to improve antigen capture efficiency to stimulate stronger immune response - Xia, Tian; Yang, Huizhu; Guo, Yuyao; Guo, Tiantian; Xin, Lingxiang; Jiang, Yanping; Cui, Wen; Zhou, Han; Qiao, Xinyuan; Wang, Xiaona; Li, Jiaxuan; Shan, Zhifu; et al. (Frontiers in Immunology, 2022)
Dendritic cells (DCs) play a key role in the natural recognition of pathogens and subsequent activation of adaptive immune responses due to their potent antigen-presenting ability. Dendritic cell-targeting peptide (DCpep) is strongly targeted to DCs, which often express antigens, to enhance the efficacy of vaccines. Our previous study showed that recombinant Lactobacillus expressing human DCpep could significantly induce stronger immune responses than recombinant Lactobacillus without DCpep, but the mechanism remains unclear. In this study, the mechanism by which DCpep enhances the immune response against recombinant Lactobacillus was explored. Fluorescence-labeled human DCpep was synthesized to evaluate the binding ability of human DCpep to porcine monocyte-derived dendritic cells (Mo-DCs) and DCs of the small intestine. The effects of Mo-DC function induced by recombinant Lactobacillus expressing human DCpep fused with the porcine epidemic diarrhea virus (PEDV) core neutralizing epitope (COE) antigen were also investigated. The results showed that human DCpep bind to porcine DCs, but not to porcine small intestinal epithelial cells. Human DCpep can also improve the capture efficiency of recombinant Lactobacillus by Mo-DCs, promote the maturation of dendritic cells, secrete more cytokines, and enhance the ability of porcine DCs to activate T-cell proliferation. Taken together, these results promote advanced understanding of the mechanism by which DCpep enhances immune responses. We found that some DCpeps are conserved between humans and pigs, which provides a theoretical basis for the development of a DC-targeted vaccine.